2016
DOI: 10.1007/s00404-016-4153-3
|View full text |Cite
|
Sign up to set email alerts
|

Gestational length assignment based on last menstrual period, first trimester crown-rump length, ovulation, and implantation timing

Abstract: PurposeUnderstanding the natural length of human pregnancy is central to clinical care. However, variability in the reference methods to assign gestational age (GA) confound our understanding of pregnancy length. Assignation from ultrasound measurement of fetal crown-rump length (CRL) has superseded that based on last menstrual period (LMP). Our aim was to estimate gestational length based on LMP, ultrasound CRL, and implantation that were known, compared to pregnancy duration assigned by day of ovulation.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…11,12 Day of ovulation provides the most accurate method for determining pregnancy duration. 13 hCG was measured (AutoDELFIA, Perkin Elmer) in late luteal phase and throughout early pregnancy in order to identify viable pregnancy and early pregnancy loss.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Day of ovulation provides the most accurate method for determining pregnancy duration. 13 hCG was measured (AutoDELFIA, Perkin Elmer) in late luteal phase and throughout early pregnancy in order to identify viable pregnancy and early pregnancy loss.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Delayed ovulation could imply a gestational length beyond 280 days, but this was not the case in a study of 59 women with a known ovulation time. Ovulation and conception were thought to happen around day 14 of the menstrual cycle, but recent studies found a median length of the follicular phase of 16 days.…”
Section: Discussionmentioning
confidence: 95%
“…Ovulation and conception were thought to happen around day 14 of the menstrual cycle, but recent studies found a median length of the follicular phase of 16 days. 15,16 Delayed ovulation could imply a gestational length beyond 280 days, but this was not the case in a study of 59 women with a known ovulation time. 16 Other clinical and large epidemiological studies, however, found a median gestational length based on last menstrual period data of 282, 1,5 283, 6,17 and 284 4 days, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Some researchers have suggested that the use of assisted reproduction data can improve dating accuracy; however, the accuracy is limited before 7 GW and is equivocal for menstrual dating beyond that GA [26], which may partly explain the considerable differences in CRL at day 45 between our study and previous studies. Additionally, CRL has been reported to overestimate gestation [27], and using CRL to determine GA has been reported to be less accurate than GA estimated by a certain LMP or day of oocyte retrieval in early pregnancy [28]; therefore, the CRL corresponding to the calculated GA is longer than the CRL of the same GA in IVF populations.…”
Section: Discussionmentioning
confidence: 99%